Enfermeiro professor: um diálogo com a formação pedagógica em cursos de lato sensu - Lauar, Chrissandra Rebouças de Souza (2012)
This research aims to identify the basic guidelines for developing a post-graduation courses of teacher training for teaching in undergraduate nursing, taking into account the training of the nurse recommended by the curriculum guidelines national. This scenario discussed is evidenced by the need to reflect a new professionalism of the educator nursing level. For this research we chose a qualitative approach in order to organize the research scenarios: post-graduation courses, training in nursing/ national curriculum guidelines and teaching in nursing. After the formation of these chapters on the link and weighing these elements, we prepared a proposal that we consider as an innovator in the educational context of nursing. The proposal that outlines, in organizing a post-graduation courses in Nursing teaching in higher education, which aims to guide the general nursing professionals working in higher teaching, improving and / or developing their pedagogical performance, through the new settings of the formation process of the nurse in contemporary society